2016
DOI: 10.1038/ncomms11577
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the boundary lateral to the shear direction of deformation twins in magnesium

Abstract: The three-dimensional nature of twins, especially the atomic structures and motion mechanisms of the boundary lateral to the shear direction of the twin, has never been characterized at the atomic level, because such boundary is, in principle, crystallographically unobservable. We thus refer to it here as the dark side of the twin. Here, using high-resolution transmission electron microscopy and atomistic simulations, we characterize the dark side of deformation twins in magnesium. It is found that the dark s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…the total Burgers vector content normal to the interface, produces tilt but no long-range strain in a bi-crystal. However, for a twin domain embedded in the matrix, this cannot be accomplished by a single type of defect, but can be produced by TDs with several Burgers vectors [8], by a set of interface dislocations with different Burgers vectors [50,51], or by a combination of interface dislocations and TDs [33]. Finally, pure steps have no long-range strain field [18].…”
Section: Equilibrium Defectsmentioning
confidence: 99%
See 2 more Smart Citations
“…the total Burgers vector content normal to the interface, produces tilt but no long-range strain in a bi-crystal. However, for a twin domain embedded in the matrix, this cannot be accomplished by a single type of defect, but can be produced by TDs with several Burgers vectors [8], by a set of interface dislocations with different Burgers vectors [50,51], or by a combination of interface dislocations and TDs [33]. Finally, pure steps have no long-range strain field [18].…”
Section: Equilibrium Defectsmentioning
confidence: 99%
“…TBs associated with {1012} twins can be observed at the atomic level, using high-resolution transmission electron microscope (HRTEM), when the beam direction is parallel to the vector λ. Thus, we refer to the view of the twin domain along the vector of λ as the 'bright side (BS)' of the twin (Figure 1(b)) [33]. The normal-TB and the forward-TB can be identified in the BS view of a twin at the atomic level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work by Wang et al [18] showed that {101 ̅ 2} tension twins can be nucleated through partial dislocation dipoles with Burgers vectors parallel to the twinning direction, forming twin embryos bounded by TBs and basalprismatic (BP) or prismatic-basal (PB) interfaces. BP/PB interfaces are asymmetric boundaries attached to TBs with a basal lattice facing a prismatic lattice (the choice of BP or PB is determined by whether the basal lattice plane is in the twin or in the matrix) [19][20][21]. In contrast to prior work on twin embryo nucleation, twin embryo growth mechanisms have been largely neglected due to the difficulties of tracking their growth process experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…During the early stages of twin growth, BP/PB interfaces make up a high fraction of the overall interfacial area separating the twin embryo from the matrix [18,22,30] and their presence makes it unclear which process controls twin embryo growth: nucleation or propagation of twinning disconnections. On the other hand, it was demonstrated both experimentally [19][20][21] and with molecular dynamics (MD) simulations [18,30] that BP/PB interfaces are present at the TTs and may even drive their motion by disconnection formation and glide on such interfaces.…”
Section: Introductionmentioning
confidence: 99%